2016
DOI: 10.1016/j.expthermflusci.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Gas entrainment behaviors in the formation and collapse of a ventilated supercavity

Abstract: The present work reports some interesting gas entrainment behaviors in the formation and collapse of a ventilated supercavity under steady and unsteady flow conditions. Our experiments show that the gas entrainment required to establish a supercavity are much greater than the minimum gas entrainment required to sustain it, and these gas entrainment values depend on Froude (Fr) number, cavitator size and the flow unsteadiness. Specifically, the measurements of the formation gas entrainment coefficients under di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…For instance, Karn et al [5], explored the ventilation hysteresis phenomenon in great detail and established that the ventilation demands to form and to sustain a supercavity may be significantly different, the latter being much smaller than the former. In a followup work, Karn et al [6] investigated the ventilation demands of the supercavity under various flow settings and provided a detailed explanation of the cavity formation and collapse processes, relating each with bubble coalescence proficiency and pressure balance near the closure. Their research has been conducted for a backward-facing model (BFM) with only a disk type cavitator.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Karn et al [5], explored the ventilation hysteresis phenomenon in great detail and established that the ventilation demands to form and to sustain a supercavity may be significantly different, the latter being much smaller than the former. In a followup work, Karn et al [6] investigated the ventilation demands of the supercavity under various flow settings and provided a detailed explanation of the cavity formation and collapse processes, relating each with bubble coalescence proficiency and pressure balance near the closure. Their research has been conducted for a backward-facing model (BFM) with only a disk type cavitator.…”
Section: Introductionmentioning
confidence: 99%
“…Their detailed analysis on the momentum balance between the air injection and the estimated re-entrant jet at the closure further supported that the re-entrant jet governs the cavity collapse process. However, although it has been reported that the ventilation demand depends crucially on the flow unsteadiness [6], which may significantly alter the operation of the supercavitating object [3,12], the investigations on ventilation demand and ventilation hysteresis to date have been limited to the steady flow conditions only. Therefore, to connect the lab-scale experiments with the practical situations of underwater vehicles encountering surface waves, experimental investigations exploring the role of different cavitator shapes and mounting strut effects in unsteady flows is needed, not only to understand general cavity behaviors, but to investigate the underlying physics with an express emphasis on the ventilation demand and ventilation hysteresis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Air cavities surrounded by the vapor sheet could promote vapor growth, resulting in an increase in the cavity shedding frequency. Karn et al (2016) proposed that operation of a supercavitating underwater vehicle is driven by an interplay between the natural and ventilated supercavitation. Effect of these two distinct modes of supercavitation on each other during supercavity formation has been systematically discussed in their recent work (Karn and Chawdhary (2018).…”
Section: Introductionmentioning
confidence: 99%